Design and development of 1-seated urban car chassis using aluminium - Fazliana, Fauzun (2010)
This thesis deals with the design and development of the 1-seated urban car chassis using aluminium. The objective of this thesis is to develop the general procedures of analyzing the existing design of Shell Eco-marathon car chassis and designing a new chassis with several enhancements using aluminium as material. The thesis describes finite element analysis techniques to predict the displacement magnitude and identify the worst stress locates in the structures. Stainless steel AISI type 304 and aluminium alloy T6 6063 were studied in this thesis which commonly used for a chassis structure in industry. The structural of three-dimensional solid modeling of the chassis was developed using Solidworks software. The strategy of validation of finite element model was developed. The finite element analysis was then performed using ALGOR Fempro. Both chassis structure was analyzed using the static stress with linear material models approaches. Finally, the displacement magnitude of the structure and worst stress are obtained. From the results, it is observed that the displacement magnitude of new chassis is decreasing about 40% compared to the existing design. The existing design which used the stainless steel as material selection also is found to have higher worst stress compared with the aluminium chassis. Besides, comparing both designs founds the overall chassis weight of aluminium chassis is reduced about 30%. The obtained results indicate that using aluminium gives the chassis structure higher stiffness and light in weight. It also found that the rectangular tubes aluminium gives stiffer structure compared to aluminium pipes. The results conclude that using aluminium with larger cross sectional tubes area gives higher stiffness chassis structure. Therefore, using rectangular tubes aluminium promising higher stiffness structure and weight saving. The durability assessment results are significant to improve the chassis design at the developing stage. The results can also significantly reduce the cost and time in fabricating the chassis during the events, and improve reliability and user confidence.